A new coating system modified with nano-sized particles for archaeological bronze protection. (July 2014) - Wang, Julin; Wu, YuQing; Zhang, Sheng
Abstract : A new coating system for archeological bronze protection that consists of a primer coating and a top coating was prepared in this study. The primer coating was prepared by mixing water-based acrylic emulsion with 1, 2, 3-benzotriazole, and the ultraviolet (UV) light-resistant top coating was prepared by mixing water-based acrylic emulsion with nano-sized TiO2 and SiO2 particles. UV light resistance and visible light transmission, contact angle, corrosion resistance, and mechanical properties of the new coating system were investigated and the results showed that UV resistance, hydrophobicity, oleophobicity, glossiness, and corrosion resistance all were improved. Application of the new system on real archaeological bronzes showed that the coating film was colorless, odorless, transparent, soft low-lustre, removable, and the original appearance of the archaeological bronze was well maintained.